2007
DOI: 10.1111/j.1365-2761.2007.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental exposure of zebrafish, Danio rerio (Hamilton), to Mycobacterium marinum and Mycobacterium peregrinum reveals the gastrointestinal tract as the primary route of infection: a potential model for environmental mycobacterial infection

Abstract: The natural route by which fish become infected with mycobacteria is unknown. Danio rerio (Hamilton) were exposed by bath immersion and intubation to Mycobacterium marinum and Mycobacterium peregrinum isolates obtained from diseased zebrafish. Exposed fish were collected over the course of 8 weeks and examined for the presence of mycobacteriosis. Mycobacteria were consistently cultured from the intestines, and often from the livers and spleens of fish exposed by both methods. Mycobacteria were not observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 40 publications
2
59
0
1
Order By: Relevance
“…Interestingly, infection with M. peregrinum was reported to be the cause of an outbreak of mycobacteriosis in an aviary containing Gouldian finches (Erythrura gouldiae) where affected birds developed granulomatous lesions of the liver and intestine (54). Another study reported that exposure of zebrafish to M. peregrinum led to clinical signs of mycobacteriosis (27). The second outlier ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, infection with M. peregrinum was reported to be the cause of an outbreak of mycobacteriosis in an aviary containing Gouldian finches (Erythrura gouldiae) where affected birds developed granulomatous lesions of the liver and intestine (54). Another study reported that exposure of zebrafish to M. peregrinum led to clinical signs of mycobacteriosis (27). The second outlier ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, transmission was significantly enhanced when the bacteria were supplied within free-living unicellular eukaryotes, including amoeba and paramecium (Harriff et al 2007;Peterson et al 2013). However, these more natural routes of transmission are not really applicable for infection experiments, as the infection dose and timing cannot be easily controlled.…”
Section: Routes Of Infectionmentioning
confidence: 99%
“…The natural infection route for M. marinum has not been fully elucidated, but the available evidence strongly indicates that the gastrointestinal tract is the port of entry (Harriff et al 2007). Furthermore, transmission was significantly enhanced when the bacteria were supplied within free-living unicellular eukaryotes, including amoeba and paramecium (Harriff et al 2007;Peterson et al 2013).…”
Section: Routes Of Infectionmentioning
confidence: 99%
“…26 M. fortuitum is a widely distributed species associated with chronic subclinical granulomatous infections. 35 M. peregrinum is relatively uncommon and is usually subclinical, 36 although a high mortality epizootic has also been reported in association with this species. 37,38 Mycobacterium spp.…”
Section: Choice Of Agentsmentioning
confidence: 99%